2011
DOI: 10.1007/s13246-011-0069-1
|View full text |Cite|
|
Sign up to set email alerts
|

ROPES eye plaque brachytherapy dosimetry for two models of 103Pd seeds

Abstract: Brachytherapy dose distributions are calculated for 15 mm ROPES eye plaque loaded with model Theragenics200 and IR06-(103)Pd seeds. The effects of stainless steel backing and Acrylic insert on dose distribution along the central axis of the eye plaque and at critical ocular structure are investigated. Monte Carlo simulation was carried out with the Version 5 of the MCNP. The dose at critical ocular structure by considering the eye composition was calculated. Results are compared with the calculated data for CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Saidi et al 16 found a depth dependent dose correction factor in their Monte Carlo study of two models of Pd-103 seeds in a 15 mm diameter ROPES plaque. A reduction of 4% due to the stainless steel backing was observed at 2 mm depth, and this reduction increased to approximately 9% at 5 mm depth.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Saidi et al 16 found a depth dependent dose correction factor in their Monte Carlo study of two models of Pd-103 seeds in a 15 mm diameter ROPES plaque. A reduction of 4% due to the stainless steel backing was observed at 2 mm depth, and this reduction increased to approximately 9% at 5 mm depth.…”
Section: Discussionmentioning
confidence: 99%
“…EBT3 film measurements without the stainless steel backing have been shown to agree with full dose to water calculations, indicating that the acrylic seed carrier has a negligible effect on the dose compared to a full dose to water assumption. Granero et al 17 and Saidi et al 16 have performed Monte Carlo simulations of the 15 mm diameter ROPES plaque, both with and without the acrylic seed carrier to assess its effect on the dose distribution. It was also found in these studies that the acrylic carrier had a negligible effect on the dose distribution.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations